FRACIONAMENTO DA MATÉRIA ORGÂNICA EM SISTEMAS DE MANEJO E USO DO SOLO - Paulino, Leonardo; Aguiar, Franciele; Feliciani, Giselle; Ensinas, Simone; Lima, Isabela; Da Silva, Jefferson (ANAIS DO ENIC, 2018)
-